Types of Carabidae (Insecta: Coleoptera) deposited at the entomological collection of Instituto- Fundación Miguel Lillo, Tucumán, Argentina - Córdoba, Silvia Patricia; Sánchez, Francisco Rolando; Bezdjian, Laura Patricia (Zootaxa, 2023)
The Carabidae (Insecta: Coleoptera) type species of Entomological Collection of the Entomology Institute housed in the Zoology Area of Miguel Lillo Foundation (FML), Tucumán, Argentina, were examined and listed. This collection is considered one of the most prestigious collections in Argentina and South America. The Carabidae family is represented by 545 species, with ten holotypes, one allotype, 12 cotypes, and 65 paratypes, which correspond to 35 species. Complete information and images for each species are given.